Implicaciones del estado nutricional materno en el peso al nacer del neonato (2009)
ABSTRACT: Malnutrition during pregnancy has been the subject of much research. Colombia’s National Nutritional Survey-2005 (ENSIN) indicated that pregnant women between (13-17, 18-29, 30-49 y of age) had anemia 52,4%, 41,3%, and 48,2%, respectively. it is not only due to iron deficiency, it is because of 5 0ut of 10 pregnant women present malnutrition ,40% are underweight, that have been associated with intra-uterine growth retardation (IUGR) and consequent low birth weight (LBW)that now is 6.2% resulting in growth retardation, infection diseases, cognitive problems and increased risk to develop chronic diseases later in life . Such evidence-based data will support recommendations and actions that will reduce health risks through nutritional modifications, and health promotion for adequate pregnancy development.